Paradoks Hukum Noodweer: Penerapan Pasal 49 KUHP dan Kedudukan Korban Begal yang Dijadikan Tersangka dalam Sistem Peradilan Pidana Indonesia - Sheren Dwi Oktaria; Inggit Setya Ningrum; Nadia Wiratama Jasmine; Dwi Mulyati (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: This study examines the legal paradox in the application of the concepts of noodweer and noodweer excess in Indonesia, particularly related to the phenomenon of victims of robbery who are named suspects after defending themselves. The study focuses on three cases that occurred in Indonesia, namely the case of Amaq Sinta in Central Lombok (NTB), DI in Medan (North Sumatra), and ZA in Malang (East Java). All three cases demonstrate the complexity of law enforcement between self-defense efforts and the limits of actions considered proportional under criminal law. Analysis of these three cases shows that the application of Article 49 of the Criminal Code often leads to incidents, especially in determining the elements of proportionality, subsidiarity, and the condition of